Kajian Komunitas Kupu-Kupu (Lepidoptera) di Kawasan Coban Watu Ondo Taman Hutan Raya Raden Soerjo - Syukron Miftakhul Khoiri; Sofia Ery Rahayu; Farid Akhsani; Fatchur Rohman (Jurnal Biosilampari : Jurnal Biologi, 2023)
This research aims to determine the composition of butterflies (Lepidoptera), analyze indices of diversity, evenness, richness, dominance and their conservation status. This research uses exploration techniques by observing and exploring 5 research stations at the research location. Sampling was carried out in March - April 2023at 07.00-12.00 WIB with 3 repetitions. Based on the results of research, butterflies that found in Coban Watu Ondo area were 21 species. Diversity index (H') 2.24 (Medium), means that the condition of the environment and ecosystem is quite good. Evenness index (E) 0.84 (High), means that the number of individuals of each species present is relatively equal and evenly distributed. Richness index (R) 3.06 (Medium), corresponds to the diversity index. Dominance index (D) 0.15 (Low), means that no species dominates. Conservation status based on IUCN shows that there are 17 species classified as not evaluated, 2 species classified as near threatened and 2 species classified as least concern.